2004
DOI: 10.1086/386331
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Gram-Negative Bacilli from Infected Neonates and Health Care Workers' Hands in Neonatal Intensive Care Units

Abstract: We sought to characterize the molecular epidemiology of gram-negative bacilli (GNB) causing infections in infants and associated with carriage on nurses' hands after hand hygiene was performed. From March 2001 to January 2003, GNB caused 192 (34%) of 562 hospital-acquired infections in the 2 participating neonatal intensive care units (NICUs) and were isolated from the hands of 45 (38%) of 119 nurses. Five species--Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Serratia marcescens and Enterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 28 publications
3
44
3
1
Order By: Relevance
“…), contaminated bottled water (10), contaminated products (eye drops, soaps, etc. ), health care workers, other contaminated patients, and sometimes the patient him-or herself (4,21,39). In neonatal intensive care units, in addition to the previously described sources, P. aeruginosa strains were recovered in contaminated feeding bottles and were associated with breast milk feeding (5,25,34).…”
mentioning
confidence: 93%
“…), contaminated bottled water (10), contaminated products (eye drops, soaps, etc. ), health care workers, other contaminated patients, and sometimes the patient him-or herself (4,21,39). In neonatal intensive care units, in addition to the previously described sources, P. aeruginosa strains were recovered in contaminated feeding bottles and were associated with breast milk feeding (5,25,34).…”
mentioning
confidence: 93%
“…S. marcescens is also well known as a nosocomial pathogen and has been responsible for outbreaks, particularly in critically ill neonates and patients in intensive care units (2,(7)(8)(9). Multidrugresistant S. marcescens strains are reported to cause more-invasive infections and tend to spread rapidly in nosocomial environments (10)(11)(12)(13). Recently, several fatal cases associated with nosocomial infections of this pathogen have been reported around the world (14,15).…”
mentioning
confidence: 99%
“…78,79,94,[132][133][134][135][136][137][138][139][140][141][142] For example, in studies conducted before glove use was common among HCWs, Ayliffe and colleagues 137 found that 15% of nurses working in an isolation unit carried a median of 1x 10 4 CFU of S. aureus on their hands; 29% of nurses working in a general hospital had S. aureus on their hands (median count, 3.8 x 10 3 CFU), while 78% of those working in a hospital for dermatology patients had the organism on their hands (median count, 14.3 x 10 6 CFU). The same survey revealed that 17-30% of nurses carried Gram-negative bacilli on their hands (median counts ranged from 3.4 x 10 3 CFU to 38 x 10 3 CFU).…”
Section: Organism Transfer To Health-care Workers' Handsmentioning
confidence: 99%
“…A study conducted in two neonatal ICUs revealed that Gram-negative bacilli were recovered from the hands of 38% of nurses. 138 …”
Section: Organism Transfer To Health-care Workers' Handsmentioning
confidence: 99%